Pengaruh Lingkungan Kerja dan Motivasi Kerja terhadap Kinerja Pegawai pada Kantor Pertanahan Kabupaten Purworejo - Lina Dwi Wulandari; Anes Arini; Hesti Respatiningsih (STIE Rajawali Purworejo, 2025)
The study aims to determine whether there is a partial and simultaneous positive and significant effect between the independent variables, namely work environment (X1) and work motivation (X2), on the dependent variable, which is employee performance (Y). The subject of this research were all employees of the Purworejo Regency Land Office who had ASN status. The sampling method uses non – probability sampling, namely saturated sampling, as many as 53 employees. The result of data analysis show that partially the work environment has a positive effect on employee performance. The work environment which includes lighting, air temperature, noise, use of color, space for movement, ability to work and relationship beetwen employees has a significant impact on employee performance.Apart from that, work motivation alsohas a positive effect on employee performance. Employee work motivation is influenced by various factor such as performance benefits, working conditions, work facilities, work performance and recognition from superiors, all of which have a direct impact on employee performance.